2006
DOI: 10.1016/j.jmaa.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Existence theorems for a class of nonlocal differential equations

Abstract: A class of nonlocal second-order ordinary differential equations of the formfor continuous f and λ is studied. The equation is supplemented with none, one, or two Robin boundary conditions depending on whether the interval of interest I is finite, semi-infinite or infinite. The only other restriction on the function λ is that it maps I into itself. Sufficient conditions for the existence of a solution are found, which include the assumption of the existence of 'upper' and 'lower' solutions. The upper and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Da Costa et al [11] showed that the solution must be unimodal. Properties of solutions have also been studied by Chang and Jau [10] and Begg [5]. The model has been applied to tumour growth [3] and the growth of plankton [4].…”
Section: Introductionmentioning
confidence: 99%
“…Da Costa et al [11] showed that the solution must be unimodal. Properties of solutions have also been studied by Chang and Jau [10] and Begg [5]. The model has been applied to tumour growth [3] and the growth of plankton [4].…”
Section: Introductionmentioning
confidence: 99%